2010
DOI: 10.1017/s003329171000036x
|View full text |Cite
|
Sign up to set email alerts
|

Emotion-modulated startle in anxiety disorders is blunted by co-morbid depressive episodes

Abstract: An anxiety disorder concurrent with a depressive episode is associated with reactivity that more closely resembles the pattern of emotional responding that is typical of depression (i.e. context insensitive) rather than the pattern that is typical for anxiety (i.e. exaggerated).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 68 publications
9
44
1
Order By: Relevance
“…However, in contrast to expectations, we observed attenuated rather than amplified SR during baseline and context conditions both before and after the explicit threat cue paradigm in the distress disorder group. Consistent with some prior research (e.g., Allen et al, 1999; Kaviani et al, 2004; Forbes et al, 2005; Lang et al, 2007; Taylor-Clift et al, 2011; Waters et al, in press), this result could be due to the inhibiting effect of depressive disorders upon SR magnitudes; 5 of the 9 adolescents in this group had a principal diagnosis of a depressive disorder. However, Grillon et al (2013) found enhanced rather than attenuated context-potentiated SR (i.e., placement of shock electrodes) in depression.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, in contrast to expectations, we observed attenuated rather than amplified SR during baseline and context conditions both before and after the explicit threat cue paradigm in the distress disorder group. Consistent with some prior research (e.g., Allen et al, 1999; Kaviani et al, 2004; Forbes et al, 2005; Lang et al, 2007; Taylor-Clift et al, 2011; Waters et al, in press), this result could be due to the inhibiting effect of depressive disorders upon SR magnitudes; 5 of the 9 adolescents in this group had a principal diagnosis of a depressive disorder. However, Grillon et al (2013) found enhanced rather than attenuated context-potentiated SR (i.e., placement of shock electrodes) in depression.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, SR modulation during emotional picture viewing in anxiety disorders is blunted by comorbid depression (Taylor-Clift et al, 2011). Depression has also been linked to diminished physiological reactivity during the anticipation of threat in conditioning experiments in offspring of mothers with a principal depressive disorder relative to offspring of mothers with a principal anxiety disorder and low risk offspring (Waters et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As was previously mentioned, studies on the association between MDD and threat responding have been extremely mixed. Some findings suggest that MDD is associated with blunted threat responding (Taylor-Clift et al, 2011; Waters et al, 2014), whereas others suggest that MDD is associated with heightened threat responding (Grillon et al, 2013; Sheline et al, 2001; Siegle et al, 2007). Meanwhile, our original analyses (Shankman et al, 2013), indicated that MDD had no impact on predictable or unpredictable threat responding.…”
Section: Discussionmentioning
confidence: 99%
“…Using startle paradigms other than NPU, it has been shown that healthy controls and individuals with a current anxiety disorder both display elevated startle potentiation when viewing unpleasant pictures; however, individuals with an anxiety disorder and comorbid depression have blunted startle (Taylor-Clift et al, 2011). Additionally, in a sample of adolescents with principal fear disorders (i.e., specific and social phobia), distress disorders (i.e., MDD, dysthymia, generalized anxiety disorder, and PTSD), and controls, Waters et al (2014) found that those with a principal fear disorder, relative to the other two groups, exhibited greater startle during safety conditions and during early phases of explicit threat (i.e., an aversive event was possible but it would not occur for another 10-50s).…”
Section: Introductionmentioning
confidence: 99%